Dilution of oral D3‐Creatine to measure creatine pool size and estimate skeletal muscle mass: development of a correction algorithm - Shankaran, Mahalakshmi; Czerwieniec, Gregg; Fessler, Chancy; Wong, Po‐yin Anne; Killion, Salena; Turner, Scott M.; Hellerstein, Marc K.; Evans, William J. (Journal of cachexia, sarcopenia and muscle, 2018)
Background Muscle mass can be measured directly in vivo by isotope dilution, using Creatine‐(methyl‐d3) monohydrate (D3‐Cr) by mouth followed by measurement of the steady‐state enrichment of D3‐creatinine (D3‐Crn) in urine. Isotope dilution methods require knowledge of the amount of tracer delivered to the pool of interest. In a subset of human subjects, a small amount of orally administered D3‐Cr ‘spills’ into urine after absorption and prior to transport into skeletal muscle cells. The objectives were to develop a method to correct for spillage to compare the estimate of muscle mass by D3‐Cr dilution to other assessments of fat‐free mass. Methods Subjects (19 males, 23–81 years old; 20 females, 20–77 years old) ingested a single dose of 60 mg D3‐Cr and urine was collected prior to and daily for 4 days following the dose. Fasting morning urine samples was assessed for D3‐Cr, total Cr, D3‐Crn, and total Crn concentrations, as well as isotopic enrichments of D3‐Crn, by LC/MS. The 24‐h urine collections over 3 days after the dose of D3‐Cr were also performed to determine D3‐Cr spillage. Total body water, fat mass, and fat‐free mass were assessed by bioelectrical impedance spectroscopy (BIS). Results Spillage of D3‐Cr in the urine was greater in women than men. D3‐Crn enrichment and the ratio of Cr/Crn were used in an algorithm to calculate Cr pool size and muscle mass. Specifically, an algorithm was developed for the estimation of spillage based on the relationship between the fasting Cr/Crn ratio and the cumulative proportion of the D3‐Cr dose excreted over 3 days based on 24‐h urine collections. Muscle mass corrected using the algorithm based on fasting urine levels correlated (r = 0.9967, P < 0.0001) with that corrected by measuring D3‐Cr dose excreted. Muscle mass measured by D3‐Crn enrichment also correlated (r = 0.8579, P < 0.0001, algorithm corrected) with that measured by 24‐h Crn excretion. Muscle mass measured by D3‐Cr dilution method correlated with intracellular water by BIS, whether using spillage corrected by the algorithm (r = 0.9041, P < 0.0001) or measured by 3 day D3‐Cr losses (r = 0.91, P < 0.0001) and similarly correlated with fat‐free mass by BIA (r = 0.8857 and 0.8929, P < 0.0001, respectively). Conclusions The D3‐Cr dilution method is further validated here as a non‐invasive, easy‐to‐use test for measuring muscle mass. The technical issue of D3‐Cr spillage can be corrected for with a simple algorithm based on fasting spot urine samples. Muscle mass by Cr dilution potentially has broad applications in clinical and research settings.